Cross-generational comparative analysis of educators communication patterns: A case study at SMPN 2 Selat, Karangasem, Bali - Ahmad Rofiki Rahman; Fenysia Alfiana (Priviet Social Sciences Journal, 2026)
This study examines the comparative communication patterns of Generation X, Generation Y (Millennials), and Generation Z teachers in the context of Natural Science (IPA) instruction at SMPN 2 Selat, Karangasem, Bali. The presence of multiple generations in school environments creates distinct communication dynamics that influence the effectiveness of classroom interactions and students’ learning experiences. Employing a qualitative descriptive approach, data were collected through classroom observations, semi-structured interviews, and documents. The analysis was conducted using Miles and Huberman’s interactive model, which involves data reduction, data display, and conclusion drawing. The findings reveal significant generational differences in verbal and nonverbal communication, technology use, and teacher–student interaction styles. Generation X teachers exhibit formal, structured, and authoritative communication with a limited integration of digital media. Generation Y teachers employ a more balanced, interactive, and expressive communication approach, supported by the moderate use of technology. Meanwhile, Generation Z teachers demonstrate highly dynamic, informal, and technology-intensive communication styles that foster horizontal and student-centered interaction. These differences reflect the influence of generational characteristics on instructional communication and indicate that cross-generational diversity enriches pedagogical practices rather than hindering them. This study contributes to educational communication research by offering empirical insights into how generational identity shapes communication behavior in classroom settings, particularly in nonurban schools. The findings also have practical implications for designing teacher professional development programs that accommodate generational differences in communicative competencies.